Anterior cruciate ligament injuries at the office workers who have irregular sport activity on the artificial surfaced playing areas - Korkmaz, Özgür; Malkoç, Melih; Gürcan, Serkan (My University, 2018)
Aim: The aim of this study is to evaluate the anterior cruciate ligament (ACL) tears in Turkish office workers on the artificial playing surfaces. Materials and Methods: Eighty-seven patients who were operated for anterior cruciate ligament tear that had injuries on artificial surfaced playing areas (ASPA)s were evaluated retrospectively. Evaluations were undertaken using Lysholm and Tegner Activity Scale pre-operatively and in the last follow-up. Injury mechanisms, shoe types, frequency of sporting activity, time of warm-up exercises before sporting activity were assessed. Types of ASPA's, body mass index (BMI) and return to work period were also determined. Results: Increase in Lysholm and Tegner activity scale between the preoperative and postoperative scores was found to be statistically significant (p<0.001). ACL tear occurred with non-contact injury in 65 patients, 22 patients had ACL tear with direct contact trauma. Football activity on the ASPAs is social allocation rather than a sportive activity. The rate of wearing special designed shoes for ASPA in sporting activities was low. The mean frequency of sporting activity was 1.4 times/month and the mean warm-up exercise time was 6.42 minutes. Sixty-nine ASPAs were made with 3th generation turf, 18 were 2nd generation turf. The mean BMI was 23.32 kg/m². The mean period for return to work was 17.41 weeks. Conclusion: Irregular sportive activity with insufficient equipment on the ASPA causes serious ACL injuries that have to be managed by surgical procedures with loss of working time and economical casualties.

Amaç: Sentetik zeminli spor alanlarında ofis çalışanlarında ortaya çıkan ön çapraz bağ yaralanmalarını değerlendirmek. Gereç ve Yöntem: Sentetik yüzeyli zeminlerde spor esnasında ön çapraz bağ yaralanması olan ve opere edilen 87 hasta retrospektif olarak değerlendirildi. Hastaların opere edilen dizleri ameliyat öncesi ve son kontrollerde Lysholm ve Tegner Aktivite Skalaları ile değerlendirildi. Yaralanma mekanizması, yaralanma esnasında kullanılan ayakkabı tipi, sportif aktivite sıklığı, sportif aktivite öncesi ısınma süresi, spor yapılan sahanın zemin tipi, vücut kitle endeksi ve işe dönüş süresi araştırıldı. Bulgular: Ameliyat öncesi ve son kontrollerdeki Lysholm ve Tegner aktivite skalalarında istatistiksel olarak anlamlı artış tespit edildi (p<0.001). Altmış beş hastada temassız travmalar sonucunda, 22 hastada ise direkt temaslı travmalar sonucunda ön çapraz bağ yırtığı oluştuğu tespit edildi. Hastaların sentetik zeminli yüzeylerde yaptıkları sportif aktiviteleri sosyal aktivite olarak gördükleri tespit edildi. Sentetik zeminli yüzeyler için uygun ayakkabı kullanımı düşük oranda idi. Hastaların aylık ortalama sportif aktivite sayıları 1.4, ortalama ısınma süresi 6.42 dk olarak bulundu. Sentetik yüzeyli sahaların 69'u 3. jenerasyon, 18'inin ise 2. jenerasyon yüzeyler idi. Hastaların ortalama vücut kitle endeksi 23.32 kg/m² idi. Cerrahi girişim sonrası işe dönüş süresi 17.41 hafta olarak belirlendi. Sonuç: Uygunsuz ekipman ve düzensiz spor aktivitesi olan kişilerin sentetik zeminli yüzeylerde yaptıkları sportif aktiviteler cerrahi tedavi gerektiren ön çapraz bağ yaralanmalarına neden olabilmektedir. Bunun sonucunda çalışma zamanında azalma ve ekonomik kayıplar ortaya çıkmaktadır.
Düzensiz spor aktivitesi olan ofis çalışanlarında sentetik zeminli yüzeylerde ortaya çıkan ön çapraz bağ yaralanmaları
Keywords: Anterior Cruciate Ligament; Artificial Playing Surface; Office Workers; Ön Çapraz Bağ; Sentetik Yüzeyli Spor Alanları; Ofis Çalışanları